Grain size and mineralogical constraints on leaching in the bottom ashes from municipal solid waste incineration: a comparison of five plants in northern Italy - Mantovani, Luciana; De Matteis, Chiara; Tribaudino, Mario; Boschetti, Tiziano; Funari, Valerio; Dinelli, Enrico; Toller, Simone; Pelagatti, Paolo (Frontiers in Environmental Science, 2023)
Introduction: Bottom ashes (BA) from municipal solid waste incinerators (MSWIs) are currently classified by the European Waste Catalogue as industrial non-hazardous waste. To promote their reuse, identification and characterization of the heavy metal-bearing phases (both glass and minerals), as well as their weathering behavior, must be addressed for what concern the chemical composition, mineralogical phases, and in high concentrations and pollutants’ mobility. An important point to be noted is whether the results from a given plant can be generalized. Materials and methods: In this work, BA from five waste-to-energy (WtE) plants in northern Italy were sorted based on different grain sizes. The area showed similar MSW production, collected from a culturally homogeneous area, and similar collection management. For each grain size, a mineralogical, chemical, and physical characterization was carried out using XRF, XRD, TGA, and the leaching test. Results and discussion: We found that for major elements, the average chemical composition of the incinerators is similar, with some differences in minor elements. Ferrara (FE) and Forlì-Cesena (FC) BA show portlandite, higher ettringite, and less amorphous than the Torino (TO), Parma (PR), and Piacenza (PC) BA. This affects the pH, the release, and toxicity of the leachates. In FE and FC ashes, ettringite is insoluble, and we not only have low sulfate but also Ni and Ba beyond reglementary limits, suggesting that Ni and Ba are present as hydroxides with portlandite, which are soluble. In TO, PR, and PC, Cr and sulfates are beyond limits, suggesting that Cr comes from dissolution in ettringite. Cu and Cl are always beyond limits; the dissolution of chlorides accounts for only 30%–35% of the global Cl leachate. We observe that in the assessment of the potential toxicity of the ashes, mineralogy has a higher effect than the bulk chemical composition. Grain size sorting, although useful together with other techniques, is not by itself able to comply with the PTE risk level. Conclusion: The findings contribute to the development of efficient treatment strategies for BA, highlighting the need for a more thorough investigation to understand composition and properties and to find innovative ways to reuse, promoting the circular economy and sustainable waste management practices.